Ammonia volatilization in response to coated and conventional urea in maize crop field - Flávio Hiroshi Kaneko; João Paulo Ferreira; Aguinaldo José Freitas Leal; Salatiér Buzetti; André Rodrigues dos Reis; Orivaldo Arf (Bioscience Journal, 2019)
The properly measurement of gas emissions and nutrient availability to crops using technologies such as polymer-coated urea are required to monitored the possible nitrogen (N) fertilizer pollution in the environment. This study aimed to evaluate N loss through ammonia volatilization from polymer-coated and conventional urea in maize field trials under two different environments. The study was carried out in Chapadão do Sul and Selvíria State of Mato Grosso do Sul evaluating the first and second harvest of maize plants. Nitrogen fertilizers were applied as polymer-coated, conventional urea and control plots were used as reference to evaluate N loss through volatilization (3, 6, 9, 12, and 15 days after fertilizer application).  The peak of ammonia volatilization was observed during the first three days after fertilizer application corresponding up to 44% of total N supplied. Polymer-coated urea had promising results showing less ammonia volatilization during the first crop. However, the same result was not observed for second crop.